Analisis Kesulitan Sisa Dalam Mengerjakan Soal Matematika Pada Pembelajaran Daring di SD Muhammadiyah 2 Kota Sorong - Sara Silalahi; Rahmatullah Bin Arsyad; Hidayani Hidayani; Muhammad Syahrul Kahar; Muhammad Fathurrahman (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this research is to be able to find out the types of difficulties faced by students and what are the factors that cause students to have difficulty working on math problems, this research was conducted on fifth grade students of SD Muhammadiyah 2 Sorong City. The method used in this research is descriptive qualitative research. The subjects of this study were 6th grade students of SD Muhammadiyah 2 Sorong City. The data collection instruments used in this study were written tests and interviews to identify errors in math problems. The results of this study are From the results of the overall data analysis, it has been shown that the most common types of errors made by students are transformation errors, procedural errors and drawing conclusions, the factors that cause errors in working on this problem occur due to internal factors which include students' attitudes in the process of learning mathematics, as well as students' low motivation in learning mathematics, as well as external factors which include difficulties in using learning media so that they are not optimal in learning, and the delivery of material provided by the teacher is not optimal